Surya Namaskar, Benefits in the Context of Physiological Perspective - Patni, Nameet Kumar; Devi, Durgawati; Jain, Sonam (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: With the recent rise in awareness in increased understanding of the importance of physical activity in promoting overall health, greater emphasis has been placed on improving physical fitness to enhance quality of life. Asian Indians have been practicing Surya Namaskar, a part of Hatha Yoga, for hundreds of years. It is frequently employed in place of a typical workout regimen. It entails a series of asanas that are performed 12 times per cycle. Although Surya Namaskar was neither considered an asana nor a part of classical Yoga, it is now regarded as a component of current yogic practices. Before starting daily tasks, performing Surya Namaskar energizes the practitioner and gives them a fully charged day. The knowledge of energy cost and physiological responses of practicing Surya Namaskar is important and forms the basis for the recommendation of regular practice as part of any training. Based on available research, we emphasize the significance of Surya Namaskar in this review by stressing its impacts on the physiological components of the body. Methods: Different Ayurveda classics, modern classics, research papers, and journals were referred to fulfill this part. Results: With the help of research references, the evaluation outlines the practice’s physical advantages in terms of improving joint mobility, extending muscle power, and promoting vitality.